Characterization of F-18 Fluorodeoxyglucose PET/CT in Granulomatosis with Polyangiitis - Nelson, Darlene Ruth; Johnson, Geoffrey B.; Cartin-Ceba, Rodrigo; Specks, Ulrich (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Objective: Granulomatosis with polyangiitis (GPA) is a rare autoimmune disease characterized by necrotizing granulomatous inflammation and small vessel vasculitis that primarily involves the upper airways, lungs, and kidneys. F-18-fluorodeoxyglucose (FDG) positron emission tomography (PET) is an imaging technique that is increasingly used in the evaluation of patients with other types of vasculitis (giant-cell arteritis). We explored the potential utility of FDG-PET/CT in the management of GPA. Methods: We identified 12 patients with GPA who underwent a total of 26 FDG-PET/CT scans from January 2005 to March 2013. The presenting clinicoradiologic features and FDG-PET/CT scans were analyzed. Results: In all patients the FDGPET/ CT scans were performed to evaluate known or suspected malignancies. Differentiation between inflammatory and malignant lesions could not be achieved based on FDG uptake intensity (maximal SUV). GPA lesions of the respiratory tract and lung were more clearly detected by FDG-PET/CT than by CT scan alone. In 3 of the 12 patients occult areas of vascular inflammation were identified that were not previously appreciated on usual organ screening in GPA. In 8 patients the FDG-PET/CT facilitated diagnosis by identifying the best biopsy site. Two patients had follow-up FDG-PET/CT scans which demonstrated decreased FDG uptake after treatment for GPA. Conclusions: FDG-PET/CT cannot differentiate between malignant and inflammatory lesions in GPA. However, occult sites of disease activity may be identified and provide a better assessment of the extent of disease activity and a more accurate assessment of treatment response. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 342-352)